Mid‐life blood pressure and microstructural white matter: Findings from the 1946 British birth cohort: Neuroimaging: Earlier life risk factors and imaging biomarkers. (7th December 2020) - Storey, Mathew; James, Sarah‐Naomi; Lane, Christopher A; Barnes, Jo; Sudre, Carole H; Parker, Thomas D; Lu, Kirsty; Keshavan, Ashvini; Buchanan, Sarah M; Keuss, Sarah E; Wagen, Aaron; Cash, David M; et al.
Abstract: Background: Mid‐life hypertension is an established risk factor for late‐life cognitive impairment. Whilst previous studies demonstrate mid‐life hypertension is associated with larger white matter (WM) hyperintensity volumes, Differences in normal appearing white matter (NAWM) microstructure may provide an earlier indication of WM injury. In a population‐based life‐course study of cognitively healthy individuals, we explored the relationship between blood pressure (BP) over 30 years and NAWM microstructural metrics in later life. Method: Participants from Insight 46, a sub‐study of the 1946 British birth cohort, underwent multi‐modal MR imaging including T1, T2, FLAIR and multi‐shell diffusion‐weighted sequences at age 69‐71. Diffusion‐weighted images were processed by automated pipelines, NAWM masks were derived by subtracting the BaMoS‐derived white matter hyperintensity mask from GIF pipeline generated WM mask (eroded by 1 voxel) using FSL. Mean values of microstructural integrity metrics (fractional anisotropy (FA), mean diffusivity (MD), neurite density index (NDI), orientation dispersion index (ODI)) were extracted from T1‐registered diffusion maps using FSL and NODDI toolbox. Individuals with a major brain or neurodegenerative disorder such as dementia, neuroinflammatory condition or stroke were excluded. Linear regression analyses examined relationships between systolic blood pressure (SBP) and diastolic blood pressure (DBP) at ages 36, 43, 53, 60‐64 and 69 and microstructural metrics at age 69‐71 adjusting for sex, age, socioeconomic class, educational attainment, childhood cognition and antihypertensive medication. Result: 379 participants were included (mean age at imaging 70.7 years, 50% female). Higher SBP at ages 53 and 69 was associated with lower FA and NDI; and higher MD, and SBP at 69 was associated with higher ODI. Similarly, higher DBP at ages 53, 60‐64 and 69 were associated with lower FA and NDI; and higher MD. There was no evidence of associations between BP at age 36 or 43 and NAWM diffusion metrics. Conclusion: Higher systolic and diastolic blood pressure from age 53 onwards are shown to be associated with differences in diffusion‐based measures of white matter microstructural integrity later in life, suggesting that systolic or diastolic hypertension in over 50's may contribute to cognitive impairment risk via alterations in NAWM microstructure differences in later life.